PECULIARITIES OF PREPARING FUTURE PRIMARY SCHOOL TEACHERS FOR USING MIND MAPS IN MATHEMATICS LESSONS - Rudenko, Nina (Educological discourse, 2020)
A great deal of information can be covered up by means of mind maps. This concept, on the basis of which the technology of mind maps was created, was introduced in the 70’s by Anthony "Tony" Peter Buzan. The author believed that the use of mind maps was most suitable for higher education and research institutes but their application is so convenient and efficient in covering up information that they are easy to use in mathematics lessons in a primary school in different ways: 1) for creating an interactive lesson plan by a teacher (a mind map that you follow during the lesson) using ICT resources; 2) creating students’ own mind maps to cover the theme of the lesson. In the article the technique of preparing future primary school teachers for using mind maps in mathematics lessons to create interactive lesson plans is substantiated. Software resources for creating mind maps are described, in particular FreeMind, Bubbl.us, MindMeister, which are useful in creating mind maps in mathematics lessons in a primary school, their positive and negative sides are identified; the algorithm of creating mind maps for a primary school student is given.